F20 Lifestyle index for individuals with HD (LifeHD): an aggregated measure that characterises the lifestyle habits of individuals with HD. (12th September 2022) - Markoulidakis, Andreas; Busse, Monica; Doheny, Emer; Drew, Cheney; Kirby, Nigel; Pallmann, Philip; ,
Abstract : Background: The impact of modifiable lifestyle factors on Huntington's Disease (HD) is an emerging area of interest in the HD community. DOMINO-HD is the first study of its kind to integrate prospective longitudinal physical activity, sleep and nutrition metrics to explore the interplay between multi-domain environmental factors and HD outcomes. Aims: Inspired by the Lifestyle for Brain Health (LIBRA) index aimed at quantifying a person's risk of developing dementia based on modifiable risk factors, we wanted to develop a similar Lifestyle Index (LifeHD) which aggregates information from a range of lifestyle factors (including physical activity, sleep, diet, and body mass index) alongside non-modifiable characteristics such as genetic information (CAG repeat length), age, and HD stage. Methods: Continuous variables are first transformed to categorical variables using recommended thresholds. Regression analysis was used to identify the range of values for each variable less likely to be linked to disease progression, with these ranges contributing zero points to the LifeHD score. These categorical variables are all included in a regression model, and the coefficients are used as characteristic-specific scores. An individual's LifeHD score is the sum of the coefficients that are relevant to its characteristics. Higher scores indicate more favourable lifestyle habits and more favourable non-modifiable characteristics. This methodology could be extended to include more characteristics. Outcome: The LifeHD association with cUHDRS progression could become a useful tool for studying the progression and severity of HD. The relationship of LifeHD score with cUHDRS (or other severity measures) would require validation on independent sample.